A Comparative Cytotoxic Evaluation of Acrylamide and Diacetone Acrylamide to Investigate Their Suitability for Holographic Photopolymer Formulations. (1st September 2013) - Cody, Dervil; Casey, Alan; Naydenova, Izabela; Mihaylova, Emilia
Abstract : The comparative cytotoxic evaluation of two monomers, diacetone acrylamide (DA) and acrylamide (AA) used in holographic photopolymer formulations, is reported. Two normal cell lines were used: BEAS-2B and HaCaT. Cellular viability was assessed using the MTT assay for three different exposure times. A difference of two orders of magnitude is observed in the lethal dose (LD50) concentrations of the two monomers. Diacetone acrylamide exhibits a significantly lower toxicity profile in comparison to acrylamide at all exposure times. This result justifies the replacement of acrylamide with diacetone acrylamide in the photopolymer formulation, with the view to reducing occupational hazard risks for large-scale holographic device fabrication. A comparative study investigating the holographic recording ability of the two photopolymers in transmission mode showed that the DA photopolymer is capable of reaching refractive index modulation values of3 . 3 × 10 - 3, which is 80% of the refractive index modulation achieved by the AA photopolymer. This makes the DA-based photopolymers suitable for a wide range of applications.